CONCEPTUAL FOUNDATIONS OF THE FORMATION OF SOCIAL PROTECTION INSTITUTIONS - Bobonov N. X. (Ecominds Press, 2025)
This article provides an in-depth analysis of the conceptual foundations of institutional approaches to ensuring social protection. The author identifies groups of institutions that serve the population—namely legal, regulatory, human capital development, and financial risk management institutions—and discusses their role in economic stability. The study highlights the importance of integrating modern innovative changes into social institutions, particularly the need to enhance efficiency through digitalization. Drawing from historical and international experiences, especially those of the United States and Asian countries, the article examines the practical outcomes of institutional reforms and emphasizes the importance of dynamic and context-sensitive institutional development. Both theoretical and practical perspectives are presented on the adaptability of institutions within socio-economic environments, their renewal mechanisms, and the principles of institutional regulation.
Keywords: Social protection, institutional change, legal institutions, economic stability, human capital, innovation, digitalization, state governance, international experience, economic crisis, social institutions.